Transformative Commitment: A new Paradigm for the Study of the Religions - Abalos, David T (Journal of Dharma, 1981)
In an excellent review of Beyond the Classics ? Essays in the Scientific Study of Religion, Gordon Clanton made three points that I shall attempt to discus in this article. First of all, he perceptively pointed out that the editors of the book were primarily concerned with exhausting the present paradigm by assuming that progress in the field consists of "gradual accumulation of empirical findings, the systematic study of hypotheses and the development of consensus with regard to a ... shared theoretical perspective " Secondly, the editors con centrate on the sociology of religion rather than on the sociology of religion. Finally, Clanton concludes that there has been a failure to move substantially beyond the classics.